(untitled) (Edukids: Jurnal Pertumbuhan, Perkembangan, dan Pendidikan Anak Usia Dini, 2020)
This research describe the effectiveness of the metaphor story as an active learning media to increase children social character. The research’s design was one group pretest-posttest design. Purposive samplingused to choose 20 students at second grade elementary school who have low social character skor. Based on teacher report, known that there were 20 student who had been lower social character than others. On this research, collecting data of child social character used observation checklist. Data was analysed by Wilcoxon Signed-Rank Test, only 19 that can analyze because one student did not complete the treatment. The result of study showed that metaphor story as active learning media increased children social character. This research describe the effectiveness of the metaphor story as an active learning media to increase children social character. The research’s design was one group pretest-posttest design. Purposive sampling used to choose 20 students at second grade elementary school who have low social character skor. Based on teacher report, known that there were 20 student who had been lower social character than others. On this research, collecting data of child social character used observation checklist. Data was analysed by Wilcoxon Signed-Rank Test, only 19 that can analyze because one student did not complete the treatment. The result of study showed that metaphor story as active learning media increased children social character.